Prosocial Arousal in Children. (2nd December 2016) - Hepach, Robert
Abstract: Children's prosociality emerges early in life, which suggests that helping others is rooted deeply in human nature. At the same time, the motivation underlying young children's instrumental helping poses a puzzle. Children do not express a specific emotion such as sympathy when removing physical obstacles for others. Instead of being motivated by a concern for others' well‐being, toddlers may act to tie up loose ends or engage in social interactions, or they may be motivated because their goals align with those of others. Recent research has addressed the underlying motivation of children's helping by directly measuring children's internal arousal via changes in the dilation of their pupils. In several studies, children's arousal in response to others' unfulfilled needs is genuinely prosocial and linked to the well‐being of others. This prosocial arousal may lie at the heart of not only children's instrumental helping but also their prosociality in general.